2021
DOI: 10.1186/s12889-021-11961-9
|View full text |Cite
|
Sign up to set email alerts
|

Ramadan daily intermittent fasting reduces objectively assessed habitual physical activity among adults

Abstract: Background Muslims around the world practice intermittent fasting during the month of Ramadan each year. We hypothesized that daily physical activity could be reduced among Muslims due to the inability to refuel and rehydrate in the fasting state. Methods A cohort study design among adults registered with national physical activity community program. Data from a pedometer-based community program was used to extract 3 months of daily step counts bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…To test the hypothesis that daily physical activity could be reduced among Muslims due to the inability to refuel and rehydrate in the fasting state, a cohort study was designed among adults registered with the national physical activity community program. 61 Data from a pedometer-based community program was used to extract 3 months of daily step counts before, during, and after Ramadan for 6 years. A survey was conducted among participants to determine fasting practice and other health and environmental factors.…”
Section: Impact Of Rf On Athletes' Well-beingmentioning
confidence: 99%
“…To test the hypothesis that daily physical activity could be reduced among Muslims due to the inability to refuel and rehydrate in the fasting state, a cohort study was designed among adults registered with the national physical activity community program. 61 Data from a pedometer-based community program was used to extract 3 months of daily step counts before, during, and after Ramadan for 6 years. A survey was conducted among participants to determine fasting practice and other health and environmental factors.…”
Section: Impact Of Rf On Athletes' Well-beingmentioning
confidence: 99%
“…Energy expenditure allows the evaluation of overall metabolic efficiency by measuring the ability to convert ingested energy into fat and protein. [ 38 ] In an attempt to maintain bodyweight during fasting, energy expenditure is decreased by reducing physical activity [ 39 ] and diet‐induced thermogenesis. [ 40 ] Supporting this, Just et al previously showed that liver‐specific LKB1 KO had decreased locomotor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Energy expenditure allows the evaluation of overall metabolic efficiency by measuring the ability to convert ingested energy into fat and protein 38 . In an attempt to maintain bodyweight during fasting, energy expenditure is decreased by reducing physical activity 39 and diet-induced thermogenesis 40 . Supporting this, Just and colleagues previously showed that liver specific LKB1 KO had decreased locomotor activity 21 .…”
Section: Discussionmentioning
confidence: 99%